The genus Chama Linne (Bivalvia) in the marine Quaternary of northern Patagonia, Argentina - Pastorino, Guido (1991)
Fil: Pastorino, Guido. División Paleozoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina